The Effect Of Improving The Quality Of Human Resources On Performance With Work Motivation As An Intervening Variable In The Regional Finance And Assets Agency Of Dairi Regency - Octo Pantas Mulianto Gultom; Muhammad isa Indrawan (Yayasan Multidimensi Kreatif, 2025)
This study aims to analyze the influence of human resource quality (HR) on employee performance with work motivation as a mediating variable in the Dairi Regency Regional Finance and Assets Agency. Superior human resource quality and high work motivation are considered important to achieve optimal performance in government organizations. A causal associative quantitative approach was used in this study, with all employees of the Dairi Regency Regional Finance and Assets Agency totaling 45 people as a sample. The data analysis technique uses Structural Equation Modeling (SEM) based on Partial Least Square (PLS) with the help of SmartPLS 3.0 software. The results of the study show that: 1) The quality of human resources does not have a significant direct influence on employee performance, with a T-statistical value of 1.067 (<1.96) and a P-value of 0.291 (>0.05); 2) The quality of human resources has a positive and significant effect on work motivation with a T-statistical value of 35.954 (>1.96) and a P-value of 0.000 (<0.05); 3) Work motivation has a positive and significant effect on employee performance, with a T-statistical value of 3.549 (>1.96) and a P-value of 0.001 (<0.05); 4) Work motivation mediates the influence between human resource quality and employee performance with a T-statistical value of 3.503 (>1.96) and a P-value of 0.001 (<0.05). These findings indicate that while the quality of HR does not directly affect performance, work motivation can be a significant mediator for strengthening those relationships. The implication of this result is that it is important for the Dairi Regency Regional Finance and Assets Agency to not only improve the quality of human resources through training and development, but also to ensure that employees remain motivated so that optimal performance can be achieved.